The Abbott PanBio WHO emergency use listed, rapid, antigen-detecting point-of-care diagnostic test for SARS-CoV-2: evaluation of the accuracy and ease-of-use - Krüger, Lisa; Gaeddert, Mary; Tobian, Frank; Lainati, Federica; Gottschalk, Claudius; Klein, Julian; Schnitzler, Paul; Kräusslich, Hans-Georg; Nikolai, Olga; Lindner, Andreas K.; Mockenhaupt, Frank P.; Seybold, Joachim; et al. (PLOS ONE, 2021)
Objectives Diagnostics are essential for controlling the pandemic. Identifying a reliable and fast diagnostic device is needed for effective testing. We assessed performance and ease-of-use of the Abbott PanBio antigen-detecting rapid diagnostic test (Ag-RDT). Methods This prospective, multi-centre diagnostic accuracy study enrolled at two sites in Germany. Following routine testing with reverse-transcriptase polymerase chain reaction (RT-PCR), a second study-exclusive swab was performed for Ag-RDT testing. Routine swabs were nasopharyngeal (NP) or combined NP/oropharyngeal (OP) whereas the study-exclusive swabs were NP. To evaluate performance, sensitivity and specificity were assessed overall and in predefined sub-analyses accordingly to cycle-threshold values, days after symptom onset, disease severity and study site. Additionally, an ease-of-use assessment (EoU) and System Usability Scale (SUS) were performed. Results 1108 participants were enrolled between Sept 28 and Oct 30, 2020. Of these, 106 (9.6%) were PCR-positive. The Abbott PanBio detected 92/106 PCR-positive participants with a sensitivity of 86.8% (95% CI: 79.0% - 92.0%) and a specificity of 99.9% (95% CI: 99.4%-100%). The sub-analyses indicated that sensitivity was 95.8% in Ct-values <25 and within the first seven days from symptom onset. The test was characterized as easy to use (SUS: 86/100) and considered suitable for point-of-care settings. Conclusion The Abbott PanBio Ag-RDT performs well for SARS-CoV-2 testing in this large manufacturer independent study, confirming its WHO recommendation for Emergency Use in settings with limited resources.
Gesehen am 22.09.2021